The influence of informal power structures on corporate strategy of a selected mining organisation in Northern Cape Province, South Africa - Kadakure, Arther (Graduate School of Business (GSB), 2023)
Corporate strategy has gained a lot of traction in academic discourse as a critical field that ensures organisational success and the role of informal structures in achieving this success has also gained a lot of focus. However, several scholars have pointed out that most of the studies on informal structures have used western and Asian socioecological narratives to contextualise informal structures. The contextual gap identified by the study and the assumptions by scholars that African, Asian and Western contexts have huge variances prompted the study to explore the contextual gap in South Africa. After defining the contextual gap, the critical question that the study sought to answer was; How are informal structures responding to corporate strategy within a South African context? To answer this question the study used an interpretive approach and a single case study to draw from the subjective experiences of 30 employees using in depth interviews. To ensure the abstraction of high-quality data the study utilised heterogeneous purposive sampling to draw insights from informed participants which in turn enabled the study to explore diversified perspectives. The study established that the socio ecological context of the organisation had both positive and negative influence on the employee's desire to accept or reject corporate strategy. The study established that the positive influence enabled smooth flow of information, flexibility, fulfilment of social needs and sharing of ideas. However, the study also established that the negative influence which manifested in resistance to corporate strategy, social fragmentation, conflict and political bickering outweighed the positive influence. The study concluded by adopting a strategic management model and extending it to contain the negative attributes of the socio-cultural environment with the hope that the model may enable the organisation to positively influence informal structures.